Systematic Identification of circRNA–miRNA–mRNA Regulatory Network in Esophageal Squamous Cell Carcinoma - Shen, Yi; Shao, Yi; Niu, Chen; Ruan, Xiaoli; Zang, Zhaoping; Nakyeyune, Rena; Guo, Xiuhua; Liu, Fen (Frontiers in Genetics, 2021)
Background: Circular RNAs (circRNAs) are recently described endogenous non-coding RNAs that have been reported to play important roles in the development and progression of cancers. This study aimed to reveal the circRNAs-related regulatory mechanism in esophageal squamous cell carcinoma (ESCC). Methods: A genome-wide circRNA microarray assay was performed to profile the expression of circRNAs in the blood of preoperative ESCC patients and healthy controls. A systematic method of data mining was performed to identify the differentially expressed miRNAs (DEmiRs) and differentially expressed genes (DEGs) based on the metaMA analysis. Bioinformatics analyses and multiple tools were employed to construct the potential circRNA–miRNA–mRNA regulatory network. Results: Thirty three differentially expressed circRNAs were identified in the ESCC blood, including 31 down-regulated and two up-regulated circRNAs in the blood of ESCC patients compared to the healthy controls. Twenty-three DEmiRNAs and 2,220 DEGs were obtained by the integration of microarray datasets. An ESCC-associated circRNA–miRNA–mRNA network was constructed based on 31 circRNAs, three DEmiRNAs and 190 DEGs. Enrichment analyses indicated that the DEGs were associated with a series of biological processes and cancer-related pathways. The protein-protein interaction (PPI) network was generated by the 190 DEGs, with 10 hub genes verified in the network. Subsequently, a sub network was established for ESCC, which included 29 circRNAs, two miRNAs and 10 hub genes. Conclusion: Our study provided a novel clue to help understand the circRNA–miRNA–mRNA regulatory mechanism, highlighting the potential roles of circRNAs in the pathogenesis and development of ESCC.